2017
DOI: 10.1002/jsfa.8597
|View full text |Cite
|
Sign up to set email alerts
|

In vitro methane and gas production with inocula from cows and goats fed an identical diet

Abstract: Goat inoculum showed higher fermentative activity with a concomitant higher CH production compared to cows. This difference highlights the ability of goats to better utilise browse species and other roughage types. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 34 publications
(59 reference statements)
2
7
0
Order By: Relevance
“…Extensive variability among individual animals with respect to the microbial species composition of the rumen, known as host individuality, is observed . Different types of substrates would cause different rumen microbial communities, and there were still variations even under uniform feeding and management conditions. , However, the differences in rumen microbial communities, which cause different fermentation efficiencies, are still unclear, and it is worth exploring these differences in subsequent studies. Some prior studies have found that the anaerobic fermentation mode of mixed inoculation could improve the efficiency of in vitro ruminal fermentation. , In the current study, the coinoculum group inoculated with biomass-normalized rumen content from goats and cows was investigated.…”
Section: Results and Dscussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extensive variability among individual animals with respect to the microbial species composition of the rumen, known as host individuality, is observed . Different types of substrates would cause different rumen microbial communities, and there were still variations even under uniform feeding and management conditions. , However, the differences in rumen microbial communities, which cause different fermentation efficiencies, are still unclear, and it is worth exploring these differences in subsequent studies. Some prior studies have found that the anaerobic fermentation mode of mixed inoculation could improve the efficiency of in vitro ruminal fermentation. , In the current study, the coinoculum group inoculated with biomass-normalized rumen content from goats and cows was investigated.…”
Section: Results and Dscussionmentioning
confidence: 99%
“…Some studies have demonstrated that the fermentative capacity of cows is higher than the fermentative capacity of goats. However, other studies reported different viewpoints . As seen from different results, a standardized in vitro ruminal fermentation system and experimental process are urgently needed to develop rumen microflora as effective resources for degrading cellulose.…”
Section: Results and Dscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the control of fermentation environment in vitro is one of the main factors leading to various results. Otherwise, it was confirmed that the rumen fermentation efficiency of cows was higher than that of goats, there were still follow-up studies that obtained the opposite results and it was difficult to give a reasonable explanation 30 . It could be seen that a standardized in vitro ruminal fermentation system and experimental process are urgently needed to develop rumen microflora as effective resources for degrading cellulose.…”
Section: Rusitecmentioning
confidence: 98%